El "Son" de Guatemala. Danza y melodía - Castellanos, J. Humberto R. (ECA: Estudios Centroamericanos, 1949)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 4, No. 35-36, 1949: 1372-1387.